The budding yeast Rad9 checkpoint complex: chaperone proteins are required for its function. - Gilbert, C; van den Bosch, M; Green, C; Vialard, J; Grenon, M; Erdjument-Bromage, H; Tempst, P; Lowndes, N (2003)
Rad9 functions in the DNA-damage checkpoint pathway of Saccharomyces cerevisiae. In whole-cell extracts, Rad9 is found in large, soluble complexes, which have functions in amplifying the checkpoint signal. The two main soluble forms of Rad9 complexes that are found in cells exposed to DNA-damaging treatments were purified to homogeneity. Both of these Rad9 complexes contain the Ssa1 and/or Ssa2 chaperone proteins, suggesting a function for these proteins in checkpoint regulation. Consistent with this possibility, genetic experiments indicate redundant functions for SSA1 and SSA2 in survival, G2/M-checkpoint regulation, and phosphorylation of both Rad9 and Rad53 after irradiation with ultraviolet light. Ssa1 and Ssa2 can now be considered as novel checkpoint proteins that are likely to be required for remodelling Rad9 complexes during checkpoint-pathway activation.